A novel constrained optimization-build method for precision assembly of aircraft engine. Issue 6 (25th September 2019) - Sun, Chuanzhi; Chen, Danyang; Li, Chengtian; Liu, Yongmeng; Liu, Zewei; Hu, Ming; Tan, Jiubin
Abstract : Purpose: This paper aims to provide a precision assembly method to improve the aircraft engine quality of initial unbalance with the purpose of founding the process for mass eccentricity propagation and demonstration of assembly process. The proposed method can be used for assembly guidance, tolerance allocation and so on, especially for the assembly with a large number of rotors and the assembly requirements of initial unbalance and coaxiality in high precision. Design/methodology/approach: This paper proposes a constrained optimization-build method to minimize initial unbalance of aircraft engine assembly, which takes amount of unbalance and concentricity of each rotor into account. A constrained nonlinear programming model is extracted by choosing the initial unbalance as the objective function, and choosing the coaxiality and assembly orientations as the nonlinear constraints. The initial unbalance is reduced stage-by-stage by controlling the assembly angle of each rotor. Findings: The validity and accuracy of the proposed method is verified by the multistage rotors assembly through experiments run with the measuring instruments. Compared with the direct-build method, the initial unbalance of final assembly using proposed method is reduced by 22.2% in four rotors assembly. Originality/value: Different from the geometric eccentricity propagation control methods to reduce the initial unbalance indirectly, this paper establishes mass eccentric propagation model in multistage rotors assembly of aircraft engine for the first time. It provides a new idea to establish the relationship between the amount of unbalance of each rotor and the initial unbalance of multistage rotors.